Evaluation of an instrument to quantify stigmatization of pregnant adolescent in Peru. - Mori Quispe, Elizabeth (2015)
Introduction: Teenage pregnancy is a public health problem that places the status of a teenager in biomedical and social vulnerability, the stigmatization of a pregnant adolescent. Objective: To evaluate psychometrically an instrument to measure stigmatization of pregnant adolescents. Design: Cross-sectional study. Location: National Maternal Perinatal Institute, Lima, Peru. Participants: Adolescent puerperae. Interventions: To 292 postpartum adolescents attended from January through May 2010 an Adolescent Pregnant Stigma Scale (APSS) consisting in 7 items was applied. For the theoretical construction of the scale, two promoter entities of social stigma were assumed: family and social environment. To assess the predictability of APSS the following hypothesis was considered: the higher levels of stigma are associated with a lower self-concept of the adolescent mother. Main outcome measures: Cronbach's alpha coefficient, medians, T student. Results: The psychometric analysis revealed for APSS a Cronbach's alpha coefficient of 0.78; two dimensions accounted for 65.8% of the total variance. Conclusions: The hypothesis was verified: a lower self-concept of the adolescent as a mother was significantly associated with higher scores of APSS (p <0.05). APSS had high consistency. There was also an association with a lower maternal self-concept, making the scale reliable and valid for use in pregnant adolescents.